STUDY OF THE MICROBIAL LANDSCAPE OF PERITONEAL EXUDATE IN ABDOMINAL INFLAMMATION - Abdreshov, S. N.; Yessenova, M. A.; Yeshmukhanbet, A. N.; Atanbaeva, G. K. (Жәңгір хан атындағы БҚАТУ, 2024)
These studies reveal the features of the composition of microorganisms in peritoneal exudate in inflammatory processes, which can lead to more effective methods of diagnosis and treatment of such conditions. Inflammation of the abdominal cavity in rats of the experimental groups was caused by intraperitoneal administration of a suspension of coprological material (feces) at a dose of 0.5 cm3.As a result of the conducted studies, it was found that on the 2nd and 5th days after infection of rats with coprological exudate into the abdominal cavity, inflammation of the abdominal organs developed, which manifested itself as an inflammatory process characterized by a disorder of blood and lymph circulation in blood and lymphatic vessels, in capillaries and venules, edema, hemorrhages in internal organs and vessels, necrosis tissues (on the 5th day after infection). In rats of the 3rd experimental group on the 3rd day after infection the condition sharply worsened, there was oppression, refusal of food, the animals crammed into a corner of the cage and did not move. Pr. mirabilis, Klebsiella spp., Listeria, Sarcina и E.coli. were isolated from samples of biological material of rats. We studied the sensitivity to 7 antibacterial drugs of isolated microorganisms, among which were Pr.mirabilis and Klebsiella spp. isolated from the abdominal cavity during inflammation. As a result of the experiment it was found that the highest sensitivity in inflammation of the abdominal cavity in rats observed highly sensitive to fluoroquinolone antibiotics, cephalosporins, and resistance to aminoglycosides and tetracycline.
Abdreshov, S. N. Study of the microbial landscape of peritoneal exudate in abdominal inflammation / S. N. Abdreshov, M. A. Yessenova, A. N. Yeshmukhanbet, G. K. Atanbaeva [et al.]. - Текст : непосредственный // Ғылым және білім=Наука и образование=Science and education. - 2024. - 1-1 (74). Ч. І. - Р. 184-192.
Keywords: peritoneum; inflammation; antibiotics; nutrient medium; sensitivity to antibiotics; научный журнал; зкату